Analysis and optimization for vibration of laminated rectangular plates with blended layers. (15th October 2021) - Innami, Michio; Honda, Shinya; Sasaki, Katsuhiko; Narita, Yoshihiro
Abstract: An accurate and straightforward analytical method is proposed for the free vibration of a laminated composite rectangular plate with blended layers. The plate with blended layers is defined here as a laminated plate where some of the outer layers are composed of multiple subareas with different orientation angles of straight fibers. A finite element code is developed as well to verify accuracy of the proposed method. In numerical comparison, the natural frequencies calculated by the present method agree well with those from the FEM code for rectangular plates with two, three, four and five subareas. Subsequently, the use of this analytical method is tested in vibration optimization, i.e. design for maximization of fundamental frequencies. This frequency optimization is formulated by changing the fiber orientation angles in multiple subareas simultaneously, and is carried out by using permutation in simple cases and by Genetic Algorithm (GA) for a larger number of frequency calculations. It is observed that introduction of blended layers is very effective approach to design the dynamic characteristics of laminated composite plates.